Reservation wages, expected wages and the duration of unemployment: evidence from British panel data - Sarah Brown; Karl Taylor (Institute for the Study of Labor (IZA), 2009)
In this paper we analyse the role of wage expectations in an empirical model of incomplete spells of unemployment and reservation wages. To be specific, we model the duration of unemployment, reservation wages and expected wages simultaneously for a sample of individuals who are not in work, where wage expectations are identified via an exogenous policy shock based upon the introduction of Working Family Tax Credits (WFTC) in the UK. The results from the empirical analysis, which is based on the British Household Panel Survey, suggest that WFTC eligibility served to increase expected wages and that expected wages are positively associated with reservation wages. In addition, incorporating wage expectations into the econometric framework was found to influence the magnitude of the key elasticities: namely the elasticity of unemployment duration with respect to the reservation wage and the elasticity of the reservation wage with respect to unemployment duration.
urn:nbn:de:101:1-20090212210
Keywords: J13; J24; J64; 330; Expected wages; reservation wages; unemployment duration; Anspruchslohn; Lohnniveau; Arbeitslosigkeit; Dauer; Großbritannien